STUDY OF THE STATE OF DEFORMATION UNDER TENSION USING FIBER GLASS REINFORCEMENTS IN BEAMS - Abobakirova Zebuniso Asrorovna; Umarov Shodiljon Abdug ‘ofurovich (Journals Park Publishing, 2022)
This master's thesis depicts an analysis of the results of research on the study of composite reinforcement elements widely used in the restoration of concrete structures of buildings and structures in the Republic of Uzbekistan and abroad.
Keywords: Composite reinforcement, concrete, load, bending moment, transverse force, consistency, deformation, deformation.